Problemática jurídica en torno a la pérdida del conocimiento tradicional (Tema Central) - Matos Jaqui, Ena G. (2014)
Since the Ecuador Constitution regulations study on community indigenous peoples rights, the loss of traditional knowledge is focused, as scenery caused from historical processes, government policies and several distinct phenomena these native people have been subdued to, such as the lifestyle change and the territory restriction. The absence of values and law protection the judicial Ecuadorian organization requires directed towards their conservation, are the present study fundaments supported by indigenous vision of the world and the reality for two local communities in the province of Sucumbíos, the Cofán Dureno and Secoya (Siekopai) San Pablo, the Applying rule to Decision 391, the related Andean norms and Biologic diversity Agreement. The article concludes with a proposal of principles that conciliate values which identify these people. The analysis ends with a propensity of principles that conciliate values that identify these people.